Antiproliferation activity of water and ethyl acetate red yeast rice fraction against MCM-B2 tumor cells - Hasim Hasim; Surya Pangidoan Nasution; Bambang Pontjo Priosoeryanto; Eka Nurul Qomaliyah (Universitas Ahmad Dahlan, 2020)
Red yeast rice (RYR), commonly known as angkak, is a functional food fermented by rice using Monascus mushrooms. It has a pigment and flavonoid content that is useful as an antioxidant and plays a role in preventing cancer or tumors. This analysis aims to test the antiproliferation activity of commercial RYR fractions of water and ethyl acetate against Miyazaki Canine Mammary Gland Tumor-Bambang 2 (MCM-B2) breast tumor cells. Research on RYR antiproliferation of cancer-sustaining MCM-B2 cells has not been previously released. In the preliminary study, the antiproliferation bioactivity was measured using the brine shrimp lethality test. The outcome of the brine shrimp lethality test showed that ethyl acetate and water fraction cytotoxicity were more than 1000 ppm and 337.07 ppm, respectively, at a lethal concentration of 50. Antiproliferative activity analyses were performed using direct hemocytometer counting. The antiproliferation activity data collected were analyzed using one-way ANOVA and Duncan continuous testing. The outcome showed that the water and ethyl acetate RYR antiproliferation activity against MCM B2 cancer cells correlated positively with the increasing concentration of each fraction. Ethyl acetate and water fractions at concentrations of 350 ppm may inhibit the growth of MCM-B2 cancer cells in vitro, reaching 42.63 percent and 39.84 percent, respectively, not significantly different (P < 0.05) with a positive doxorubicin control of 41.24 percent. In conclusion, the ethyl acetate and water fraction of RYR have potent antiproliferation activity against MCM-B2 breast tumor cells.